2016
DOI: 10.46538/hlj.13.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Cross-language Influence in the Stop Voicing Contrast in Heritage Tagalog

Abstract: In heritage bilinguals’ sound structure, some aspects of the sound system are more prone to cross-language influence than others. In this study, we compare two different models of crosslanguage influence, a phonological markedness based model, which proposes that influence selectively affects a phonologically marked structure, and a phonetic category based model, where influence is mediated through cross-language equivalence classification of similar phones. The empirical data for the study comes from the prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Another finding of the current study is that, although HL learners showed patterns similar to L1 Korean speakers in terms of manipulating two acoustic cues, VOT and f0 values were noticeably higher in HL learners than in L1 Korean, as seen in Figure 6. This finding seems to support the claim that although HL learners have an advantage over L2 learners regarding phonological and phonetic contrasts, HL speakers' production is significantly different from that of L1 speakers (Asherov, Fishman, & Cohen, 2016;Chang, Yao, Haynes, & Rhodes, 2011;Flores & Rato, 2016;Kang, George, & Soo, 2016;Rao, 2015;Ronquest, 2013). We suggest that the higher VOT and f0 in HL learners of the current study than in L1 Korean might be the result of the enhancement effect of a clear speaking style.…”
Section: Comparison Between Hl L1 Korean and L2 Learners Of Koreansupporting
confidence: 76%
See 1 more Smart Citation
“…Another finding of the current study is that, although HL learners showed patterns similar to L1 Korean speakers in terms of manipulating two acoustic cues, VOT and f0 values were noticeably higher in HL learners than in L1 Korean, as seen in Figure 6. This finding seems to support the claim that although HL learners have an advantage over L2 learners regarding phonological and phonetic contrasts, HL speakers' production is significantly different from that of L1 speakers (Asherov, Fishman, & Cohen, 2016;Chang, Yao, Haynes, & Rhodes, 2011;Flores & Rato, 2016;Kang, George, & Soo, 2016;Rao, 2015;Ronquest, 2013). We suggest that the higher VOT and f0 in HL learners of the current study than in L1 Korean might be the result of the enhancement effect of a clear speaking style.…”
Section: Comparison Between Hl L1 Korean and L2 Learners Of Koreansupporting
confidence: 76%
“…However, although HL speakers' ratings were considerably closer to monolinguals' average ratings, HL speakers' ratings were also significantly different from monolinguals' ratings in that they showed more variation. Similarly, Kang, George, and Soo (2016) found that English-speaking Tagalog HL speakers' productions of voiceless stops in English and Tagalog closely approximated native speakers' productions of their two languages (including stress effects), but that voiced stops displayed substantial cross-language influence and assimilatory stress effects in both languages. Finally, in a recent study on Spanish heritage speakers, Kim (2019) observed that they diverged from monolinguals and performed similarly to L2 learners in the production of stress-based minimal pairs, showing substantial overlap between the two stress patterns.…”
Section: Heritage Language (Hl) Learners' Phonology and Phonetics And...mentioning
confidence: 82%
“…The phonetic realization of the phonological stop contrast in “true voicing” languages (where the /p-b/ contrast is realized as [p-b]), as compared to a language with an aspiration contrast (where /p-b/ is realized as [pʰ-p]), has served as the primary testing ground for cross-language influence in consonantal distinctions (e.g. Fowler et al, 2008 for French; Flege & Eefting, 1987b for Spanish; Kang et al, 2016 for Tagalog). This work generally shows that relatively proficient L2 speakers, even late learners, differentiate cross-language corresponding segments, even if they do not match monolingual norms.…”
Section: Introductionmentioning
confidence: 99%
“…While such early exposure places heritage speakers at an advantage over late L2 learners, this acquisition trajectory, coupled with L2 dominance, also makes heritage speakers incomparable to native speakers who are more dominant in the L1 (C. B. Chang et al, 2011; Godson, 2004; Kan, 2020; Kang et al, 2016; Saadah, 2011). And although some speech sound categories are shared by the L1 and L2 (e.g., C.…”
Section: Heritage Speaker Phonologymentioning
confidence: 99%